1989
DOI: 10.1523/jneurosci.09-02-00528.1989
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral target choice by homologous neurons during embryogenesis of the medicinal leech. II. Innervation of ectopic reproductive tissue by nonreproductive Retzius cells

Abstract: Most Retzius (Rz) cells innervate the body wall of their own and adjacent segments, whereas Rz cells in segments 5 and 6 [Rz (5,6)] innervate the reproductive tissue, which is found only in those segments. Results from the preceding paper (Loer and Kristan, 1989a) showed that Rz (5,6) and standard Rz cells do not normally compete for their respective peripheral targets. These experiments did not, however, distinguish between 2 other possible mechanisms of target selection: intrinsic differences in target prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In addition, studies in the leech have demonstrated that the Retzius cells which innervate the reproductive tissue differ in morphology from Retzius cells in other segments which innervate the body musculature (Glover and Mason, 1986;Jellies et al, 1987). Extirpation and transplantation experiments have demonstrated that the development of a characteristic morphology by the reproductive Retzius neurons requires contact with the reproductive tissue Loer and Kristan, 1989). Finally, examination of sensory systems suggests that peripheral targets can retrogradely influence the central synaptic connections made by primary sensory neurons as well as the neuropeptides that those neurons contain ( Horgan and van der Kooy, 1992;McMahon and Gibson, 1987;Frank, 1987,1988).…”
Section: Not Only Retrograde But Also Anterograde Signalling Is Reqmentioning
confidence: 99%
“…In addition, studies in the leech have demonstrated that the Retzius cells which innervate the reproductive tissue differ in morphology from Retzius cells in other segments which innervate the body musculature (Glover and Mason, 1986;Jellies et al, 1987). Extirpation and transplantation experiments have demonstrated that the development of a characteristic morphology by the reproductive Retzius neurons requires contact with the reproductive tissue Loer and Kristan, 1989). Finally, examination of sensory systems suggests that peripheral targets can retrogradely influence the central synaptic connections made by primary sensory neurons as well as the neuropeptides that those neurons contain ( Horgan and van der Kooy, 1992;McMahon and Gibson, 1987;Frank, 1987,1988).…”
Section: Not Only Retrograde But Also Anterograde Signalling Is Reqmentioning
confidence: 99%
“…The medicinal leech, an annelid worm, has been widely used to study the neuronal basis of behavior and development of the central nervous system (Muller et al, 1981;Loer and Kristan, 1989;French et al, 1992;Drapeau et al, 1995). Although early development of this leech has been previously described in a paper covering early embryonic organization and segmentation, which occur during approximately the first half of embryogenesis (Fernandez and Stent, 1982), the last half of embryogenesis has remained less well categorized.…”
mentioning
confidence: 99%
“…However, Rz5 and Rz6 cells do not grow further in search of their missing targets but, instead, innervate body wall tissues, acquiring the samc phenotype as their segmental homologs. In experiments in which a target was transplanted to an ectopic position, the local Rz cells were able to innervate it and acquired at least part of the Rz5,6 phenotype, including the retraction of interganglionic projections (Loer and Kristan, 1989). A similar result is found in animals with naturally occurring ectopic targets (Macagno, Peinado, and Stewart, 1986).…”
Section: For Some Leech Neurons Direct Interaction With the Target Dmentioning
confidence: 65%